2022
DOI: 10.31635/ccschem.021.202101111
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Hydrophilic Porous Photothermal Membranes for Durable and Highly Efficient Solar-Driven Interfacial Water Evaporation

Abstract: It is highly desirable to develop a solar-driven interfacial water evaporator with a self-healing ability and highefficiency water evaporation performance for water distillation and desalination, but it is still considerably challenging. Herein, by exploiting the advantages of the self-healing hydrophilic polymer, a self-healing hydrophilic porous photothermal (SHPP) membrane is fabricated by the curing of a mixture of a self-healing hydrophilic polymer, carbon black, and NaCl, followed by the removal of NaCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…On 22 March 2021, World Water Day raised awareness of the global water crisis and appealed to valuing water to support the achievement of Sustainable Development Goal 6: availability and sustainable management of water and sanitation for all by 2030 . To address this issue and achieve the goal of carbon peak by 2030 and carbon neutralization by 2060, researchers focused on finding sustainable sources of freshwater by harvesting water from atmospheric fog, ,,, producing water from saline water desalination, ,,,, and wastewater treatment. ,,, …”
Section: Application and Outlook Of Overflow Control For Sustainable ...mentioning
confidence: 99%
See 2 more Smart Citations
“…On 22 March 2021, World Water Day raised awareness of the global water crisis and appealed to valuing water to support the achievement of Sustainable Development Goal 6: availability and sustainable management of water and sanitation for all by 2030 . To address this issue and achieve the goal of carbon peak by 2030 and carbon neutralization by 2060, researchers focused on finding sustainable sources of freshwater by harvesting water from atmospheric fog, ,,, producing water from saline water desalination, ,,,, and wastewater treatment. ,,, …”
Section: Application and Outlook Of Overflow Control For Sustainable ...mentioning
confidence: 99%
“…In recent years, with the emergence of biomimetic interface research, bioinspired materials with superwettabilities and topological structures were fabricated and used to control liquid–solid interfacial action. ,, Superwettability as a new scientific discovery and a fully commercialized technology has been listed as one of the top ten emerging technologies of chemistry projects in 2021, which possesses a great capacity to contribute to the well-being of society and the sustainability of the earth, and open new opportunities in chemistry and beyond . Research on fundamental interface problems has gradually shifted from static to dynamic ,, such as liquid impact, transport, breakup and dripping, bursting, etc., from kinetic processes to thermodynamic processes such as icing and melting, , frosting, dewing, thermal cooling, evaporation and crystallization, ,,,, cooling crystallization, and boiling. , In nature, many organisms can survive under harsh conditions via skillfully manipulating liquid overflow using their unique surface structures. In addition, the overflow phenomenon is common in many applications ranging from macroscale water jets, microfluidic chips, to nanoscale spinning.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1 M H 2 SO 4 or NaOH wastewater, the ER of SHCSC was maintained at 2.2 kg m −2 h −1 . Xu et al 53 reported the preparation of self-healing hydrophilic porous photothermal membranes (PU 20 /CB 0.5 /NaCl 5 membranes), which exhibited an ER of 1.68 kg m −2 h −1 . After soaking in 1 wt% CH 3 COOH (pH = 2.8) and 1 wt% Na 2 CO 3 (pH = 11.7) solution for 10 days, the porous structure of the material was stable.…”
Section: Function Of Pms Of Sdie For Water Treatmentmentioning
confidence: 99%
“…Given the abundance and sustainability of sunlight, harnessing solar energy to produce freshwater has drawn increasing attention over the past years. Volumetric evaporation or nanofluid systems would typically lead to severe heat loss below the water–air interface . In comparison, the localized solar–thermal conversion in the interfacial evaporation process simultaneously applies most of the heat to the liquid–vapor phase transition and improves the evaporation efficiency, which is promising in the field of water purification.…”
Section: Introductionmentioning
confidence: 99%